2010
DOI: 10.3892/etm_00000076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-operative transcatheter arterial chemoembolization for resectable hepatocellular carcinoma: Implication of circulating cancer cells by detection of α-fetoprotein mRNA

Abstract: Abstract. transcatheter arterial chemoembolization (tacE) is useful for the treatment of multiple hepatocellular carcinomas (hccs). pre-operative tacE is used to reduce recurrence caused by peri-and post-operative spread of cancer cells; however, the efficacy is controversial. In this study, we evaluated the efficacy of pre-operative TACE for HCC and the implication of circulating cancer cells, retrospectively. We analyzed 495 patients with hcc who had undergone hepatectomy between 1980 and 2006, including 252… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Previous research on TACE clarified that a higher AFP value was an independent risk factor for tumor recurrence and metastasis. 26,27 In our study, abnormal AFP values were demonstrated to be a significant predictor only in group C, but not in the other two groups. AFP is secreted by cancerous or regenerated hepatocytes, 28 and decreasing AFP values after transarterial therapies were considered to be the result of tumor hypoxia and necrosis 29 and were thought to indicate a positive response to treatment.…”
Section: Bjrmentioning
confidence: 40%
“…Previous research on TACE clarified that a higher AFP value was an independent risk factor for tumor recurrence and metastasis. 26,27 In our study, abnormal AFP values were demonstrated to be a significant predictor only in group C, but not in the other two groups. AFP is secreted by cancerous or regenerated hepatocytes, 28 and decreasing AFP values after transarterial therapies were considered to be the result of tumor hypoxia and necrosis 29 and were thought to indicate a positive response to treatment.…”
Section: Bjrmentioning
confidence: 40%
“…1 Advances in surgical techniques and perioperative care have greatly improved the outcome of hepatic resection for HCC. [2][3][4] Nonetheless, long-term survival after hepatectomy remains unsatisfactory, due to the high incidence of recurrence or metastasis. For these recurrent HCCs, inducing hypoxia by intercepting the hepatic arterial blood flow, i.e., transarterial chemoembolization (TACE), has achieved a pronounced therapeutic effect.…”
mentioning
confidence: 99%
“…In liver transplant recipients with HCC, preoperative AFP mRNA positivity is a risk factor for recurrence [12] , while the detection of AFP mRNA before surgery in patients undergoing TACE is associated with worse survival [13] . In addition to these risks associated with preoperative AFP mRNA, many authors have demonstrated that the rate of AFP mRNA positivity is increased after hepatectomy, as was shown in our data [1-3, 6, 14-16] .…”
Section: Discussionmentioning
confidence: 99%